THE USE OF LCD PROJECTORS IN THE LEARNING PROCCES AND LEARNING MOTIVATION TOWARDS LEARNING ACHIEVEMENT IN THE IPS COURSE - Jani, Jani (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The success of education in realizing quality human resources can be measured through learning achievement, which is greatly influenced by several factors, including the use of LCD Projector media in learning and learning motivation. Liquid Crystal Display (LCD) is currently widely used as a computer screen as well as a Notebook or Laptop which, when combined with a projector, can be used as a sufficient learning medium. The display produced on a screen that is wide enough at 2 x 2 meters is very suitable for use in classes with a large number of students. The combination of a Laptop (Notebook) with an LCD Projector can present learning material according to the design prepared by a lecturer. With the design of messages/materials, it can take the form of: Audio, Visual Silent, Visual Motion, or Audio Visual Motion. With full color display, it is very attractive to students’ interest and attention in following the learning process.The purpose of this research is 1). to find out whether there is a significant influence of students’ perceptions of the use of LCD Projectors in the learning process on the learning achievement of IPS courses for Semester IV students of PGMI Faculty of Tarbiyah and Teaching UIN Sayyid Ali Rahmatullah Tulungagung Academic Year 2021/2022 ?. 2). to find out whether there is a significant influence of the level of learning motivation on the learning achievement of IPS courses for Semester IV students of PGMI Faculty of Tarbiyah and Teaching UIN Sayyid Ali Rahmatullah Tulungagung Academic Year 2021/2022 ?. 3). to find out whether there is a joint significant influence of students’ perceptions of the use of LCD Projectors in learning and the level of learning motivation on the learning achievement of IPS courses for Semester IV students of PGMI Faculty of Tarbiyah and Teaching UIN Sayyid Ali Rahmatullah Tulungagung Academic Year 2021/2022.